A Single-Plasmid Inducible-Replication System for High-Yield Production of Short Ff (f1, M13 or fd)-Phage-Derived Nanorods - León-Quezada RI; Miró MG; Khanum S; Sutherland-Smith AJ; Gold VAM; Rakonjac J (John Wiley and Sons Ltd., 2025)
Ff (f1, M13 or fd) filamentous phages have been used for myriad applications including phage display, assembly of nanostructures and as carriers of agents used for diagnostic and therapeutic purposes. Recently, short Ff phage-derived functionalised nanorods have emerged as a superior alternative to full-length filamentous phages for applications from lateral flow assays to cell- and tissue-targeting. Their advantages, such as shorter length and the lack of antibiotic resistance genes, make them particularly promising for expanding the current scope of Ff bionanotechnology and biomedical applications. Limitations to the widespread use of Ff-derived nanorods include a requirement for two plasmids and the relatively low production efficiency. This is due to the presence of only the positive Ff origin of replication, allowing replication of only the positive strand. Here we describe a single-plasmid negative origin-containing inducible-replication system for nanorod production. These improvements simplify and increase nanorod production by two orders of magnitude compared with the constitutive positive origin-only production system. The high concentration of nanorods allows formation of higher-order structures, such as stacks and rafts, as imaged by transmission electron microscopy. In summary, our system will facilitate production and expand the applications of Ff-derived biological nanorods.
Keywords: DNA origami; f1 phage; fd phage; filamentous bacteriophages; M13 phage; nanoparticles; nanorods